2015
DOI: 10.1002/erv.2412
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Body Image and Sexual Functioning in Bariatric Surgery Patients

Abstract: This article provides an overview of the literature on quality of life, body image and sexual behaviour in individuals with extreme obesity and who undergo bariatric surgery. Quality of life is a psychosocial construct that includes multiple domains, including health-related quality of life, weight-related quality of life, as well as other psychological constructs such as body image and sexual functioning. A large literature has documented the impairments in quality of life and these other domains in persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 45 publications
(72 reference statements)
0
54
0
Order By: Relevance
“…Possible nonobesity-related barriers include low self-efficacy, negative weight bias internalization [60], or low motivation to reduce a sedentary lifestyle [59]. In the postoperative group, positive weight-related effects that can arise as early as few months after surgery [61][62][63] might have lessened the motivation to behavioral changes in some patients. Furthermore, whether a person is prone to engage in habitual PA may be at least partly determined by genetic [22,64] or temperamental factors [65].…”
Section: Resultsmentioning
confidence: 97%
“…Possible nonobesity-related barriers include low self-efficacy, negative weight bias internalization [60], or low motivation to reduce a sedentary lifestyle [59]. In the postoperative group, positive weight-related effects that can arise as early as few months after surgery [61][62][63] might have lessened the motivation to behavioral changes in some patients. Furthermore, whether a person is prone to engage in habitual PA may be at least partly determined by genetic [22,64] or temperamental factors [65].…”
Section: Resultsmentioning
confidence: 97%
“…First, HRQOL is assessed with numerous questionnaires, since there is no specific questionnaire to assess HRQOL in bariatric surgery patients [5, 6]. Second, weight loss might also influence HRQOL [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that following weight loss interventions, subjects experience significant improvements in weight‐related quality of life with improvements often occurring early in the weight loss experience when weight loss is rapid . IWQOL‐Lite was previously measured in four randomized double‐blind NB phase 3 trials for 56 weeks .…”
Section: Discussionmentioning
confidence: 99%